The Formation of the Integral Human Being from the Perspective of Consciousness: Ibn Sina and Santiago Ramón y Cajal - Rahmad Ramadhan; Ridha Ahida (Journal of Indonesian Islamic Studies, 2026)
The formation of the integral human being requires an understanding of biological, intellectual, spiritual, and moral dimensions. However, studies integrating Islamic philosophy and modern neuroscience in explaining this formation remain limited. This study examines the concepts of consciousness proposed by Ibn Sina and Santiago Ramón y Cajal and formulates a conceptual synthesis for integral human development. Using library research with a comparative approach, the study analyzes Ibn Sina’s Aḥwāl al-Nafs and Al-Najāh, alongside Cajal’s Texture of the Nervous System of Man and the Vertebrates and Advice for a Young Investigator. Data were analyzed through concept identification, classification, comparison, interpretation, and synthesis. The findings show that Ibn Sina understands consciousness as a manifestation of the soul (al-nafs) actualized through intellect (al-‘aql) toward intellectual, spiritual, and moral maturity. In contrast, Cajal explains consciousness through neuronal organization, the nervous system, and neuroplasticity as the biological basis of cognition. These perspectives are complementary, producing a model of integral human formation that unifies biological, intellectual, spiritual, and moral dimensions. This study contributes to interdisciplinary scholarship and provides a holistic foundation for education, character development, and future human-development research.